The Torradovirus‐specific RNA2‐ORF1 protein is necessary for plant systemic infection. (20th December 2017) - Ferriol, INMACULADA; Vallino, MARTA; Ciuffo, MARINA; Nigg, JARED C.; Zamora‐Macorra, ERIKA J.; Falk, BRYCE W.; Turina, Massimo
Summary: Tomato apex necrosis virus (ToANV, species Tomato marchitez virus, genus Torradovirus, family Secoviridae ) causes a severe tomato disease in Mexico. One distinctive feature of torradoviruses compared with other members of the family Secoviridae is the presence of an additional open reading frame (ORF) in genomic RNA2 (denominated RNA2‐ORF1), located upstream of ORF2. RNA2‐ORF2 encodes a polyprotein that is processed into a putative movement protein and three capsid proteins (CPs). The RNA2‐ORF1 protein has homologues only amongst other torradoviruses and, so far, no function has been associated with it. We used recombinant and mutant ToANV clones to investigate the role of the RNA2‐ORF1 protein in various aspects of the virus infection cycle. The lack of a functional RNA2‐ORF1 resulted in an inability to systemically infect Nicotiana benthamiana and tomato plants, but both positive‐ and negative‐strand RNA1 and RNA2 accumulated locally in agroinfiltrated areas in N. benthamiana plants, indicating that the RNA2‐ORF1 mutants were replication competent. Furthermore, a mutant with a deletion in RNA2‐ORF1 was competent for virion formation and cell‐to‐cell movement in the cells immediately surrounding the initial infection site. However, immunological detection of the ToANV CPs in the agroinfiltrated areas showed that this mutant was not detected in the sieve elements even if the surrounding parenchymatic cells were ToANV positive, suggesting a role for the RNA2‐ORF1 protein in processes occurring prior to phloem uploading, including efficient spread in inoculated leaves.